1977
DOI: 10.1029/ja082i025p03577
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of auroral currents measured by the Chatanika Radar With 50-MHz backscatter observed from Anchorage

Abstract: Auroral electrojet parameters measured by the Chatanika incoherent scatter radar have been compared with VHF backscatter observed in a comparable spatial area by the 50‐MHz auroral radar located at Anchorage. We find that the D region absorption, occurring in concert with the morning (westward) electrojet, can significantly decrease the observed scatter amplitude. If the amplitude is corrected for absorption effects, we find that the scatter varies approximately linearly with either eastward or westward curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Strong experimental evidence for this relationship has been found recently by ECKLUND et al (1977) andCAHILL et al (1978). The only serious problem in observing auroral zone electric fields with this type of radar is that a threshold electric field apparently is needed to excite the plasma irregularities in the ionosphere (TSUNODA and PRESNELL, 1976;SIREN et al, 1977). CAHILL et al (1978) found threshold values of 15-20mVm-1 for the STARE radars.…”
Section: Instrumentationmentioning
confidence: 81%
See 1 more Smart Citation
“…Strong experimental evidence for this relationship has been found recently by ECKLUND et al (1977) andCAHILL et al (1978). The only serious problem in observing auroral zone electric fields with this type of radar is that a threshold electric field apparently is needed to excite the plasma irregularities in the ionosphere (TSUNODA and PRESNELL, 1976;SIREN et al, 1977). CAHILL et al (1978) found threshold values of 15-20mVm-1 for the STARE radars.…”
Section: Instrumentationmentioning
confidence: 81%
“…GREENWALD (1979) has shown that in the auroral E layer the net drift velocity of the irregularities is nearly a pure EXB drift and that, therefore, the transverse ionospheric electric field vector is orthogonal and proportional to the measured drift velocity vector. Strong experimental evidence for this relationship has been found recently by ECKLUND et al (1977) andCAHILL et al (1978). The only serious problem in observing auroral zone electric fields with this type of radar is that a threshold electric field apparently is needed to excite the plasma irregularities in the ionosphere (TSUNODA and PRESNELL, 1976;SIREN et al, 1977).…”
Section: Instrumentationmentioning
confidence: 86%
“…Since these waves can grow to large amplitudes without saturating [Sudan et al, 1973], the growth times can be correspondingly large; numerical modeling for the equatorial electrojet [McDonald et al, 1974[McDonald et al, , 1975 suggest times of more than 1 s. From the times given in Table 2, it appears that if these waves are confined to the lower E region (as might be expected in the premidnight period) they may not reach saturation (or even the nonlinear regime) before encountering conditions of marginal stability, whereas the longer times available in the upper E region (a growth region in the post midnight period if the E region peak is low) would permit larger wave amplitudes. This might explain why it was in the morning sector that Siren et al [1977] observed auroral echoes coincident with electric fields of only 10 mV/m (which implies the involvement of the gradient-drift instability).…”
Section: Energy Propagation and Wave Amplitudesmentioning
confidence: 98%
“…SIREN et al (1977) have compared the auroral electrojet parameters measured at Chatanika with the 50MHz auroral radar data from the backscatter radar located Note the large amplitude D-and Z-component oscillations. at Anchorage.…”
Section: Field-aligned Currents and Ionospheric Electrojet Currents Imentioning
confidence: 99%